Imprints of tropical cyclone on three-dimensional structural characteristics of mesoscale oceanic eddies - Zhang, Zheliang; Zheng, Yunxia; Li, Hao (Frontiers in Earth Science, 2023)
The impact of tropical cyclones (TCs) on the three-dimensional characteristics of mesoscale oceanic eddies is investigated in this study on the basis of statistical analysis by satellite-based eddy information and Argo data. By comparing the three-dimensional structure of the temperature, salinity, and geostrophic velocity in the upper ocean above 1000 meters depth, it was found that there is a heat pump effect in the changes of eddy structure similar to that in tropical cyclones. Under the forcing of TC, the abnormal signals in the strong cold core (warm core) structure originally existing in the upper layer of the cyclonic eddy (anticyclonic eddy) are transmitted to the middle and lower layers of the eddy and form retention, making the eddy structure not recover to the original state in a short period of time. To a certain extent, this shows that the influence of TC on the eddy structure is not limited to the ocean surface. At the same time, the change of barrier layer in the eddy is explored, and it was found that the barrier layer thickness in both cyclonic eddy and anticyclonic eddy has increased, which also confirms the previous research.